A Double-Blind, Randomized Controlled Trial of Hydroxychloroquine for Cognitive Dysfunction and Inflammatory Biomarkers in Systemic Lupus Erythematosus Patients in Indonesia - Bantar Suntoko; Suharyo Hadisaputro; Handono Kalim; Suyanto Hadi; Ika Vemilia Warlisti (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Systemic lupus erythematosus (SLE) is an autoimmune condition characterized by persistent, chronic inflammation that damages organ tissue. One of the symptoms that is often found in SLE is cognitive dysfunction. Hydroxychloroquine is recommended for the treatment of all levels of SLE. This study was conducted to prove the influence of hydroxychloroquine on improving cognitive function and inflammatory biomarkers compared to standard therapy.METHODS: The study adopted randomized controlled trial (RCT) in SLE patients with cognitive dysfunction who met the inclusion criteria. The treatment group consisted of 26 subjects who received hydroxychloroquine 200 mg/day for 8 weeks and standard therapy, while the control group consisted of 29 subjects who were given standard therapy only. Examination of Montreal Cognitive Assessment (MoCA)-INA, interleukin (IL)-6, IL-4, interferon (IFN)-α, and C-reactive protein (CRP) scores was carried out at the beginning and the end of the study. The unpaired variables were examined with independent T-test or the Mann-Whitney test, while the paired variables were examined with paired T-test or Wilcoxon signed rank test. The Spearman correlation test was used to measure correlation between variables.RESULTS: A total of 55 subjects participated and completed the study. The result showed a significant relationship between hydroxychloroquine and decreasing levels of IL-6 and IL-4 (p<0.05). Meanwhile, there was no significant effect on the increase in cognitive function and decrease in IFN-α and CRP (p>0.05) in both groups.CONCLUSION: Hydroxychloroquine decreases the levels of IL-6 and IL-4, but has no effect on cognitive function, levels of IFN-α and CRP.KEYWORDS: hydroxychloroquine, systemic lupus erythematosus, cognitive dysfunction, inflammation